2020
DOI: 10.4236/jgis.2020.125029
|View full text |Cite
|
Sign up to set email alerts
|

Multitemporal Analysis of Land Use and Coverage in the Low Course of the Araguaia River

Abstract: This work aimed to analyze the spatial behavior of plant formations and land use in the Ecological Tension Area Amazon-Cerrado. To this end, the Araguaia river basin was selected, in its low course, because it constitutes a physical-natural limit between the two Biomms, with intense dynamics of use and land cover Thus, in addition to researching scientific references and socioeconomic data from secondary sources, a geographic database was elaborated, with georeferenced data, and spatial operations are carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…This can be seen in the increase to 3,180.7 km² in the water mass in recent decades. For the Araguaia Lower region, Oliveira et al (2020) observed similar changes in land use and cover in relation to the advance of pasture and agriculture, with the expansion of the latter class being attributed to public policy incentives and government investments. In this way, the authors discussed how much this environmental degradation will affect local ecosystems, since native forests are being deforested with the two banks, right and left, of this stretch of the Araguaia River being marked by different forms of land use such as agriculture and pasture.…”
Section: La Niñamentioning
confidence: 80%
“…This can be seen in the increase to 3,180.7 km² in the water mass in recent decades. For the Araguaia Lower region, Oliveira et al (2020) observed similar changes in land use and cover in relation to the advance of pasture and agriculture, with the expansion of the latter class being attributed to public policy incentives and government investments. In this way, the authors discussed how much this environmental degradation will affect local ecosystems, since native forests are being deforested with the two banks, right and left, of this stretch of the Araguaia River being marked by different forms of land use such as agriculture and pasture.…”
Section: La Niñamentioning
confidence: 80%
“…The use of TerraClass project data allowed qualifying the deforestation identified by PRODES that coincided with cocoa properties. Thus, for the multitemporal analysis of land use and land cover in cocoa properties, transition matrices were used [31] [32].…”
Section: Land Use and Covermentioning
confidence: 99%